Introducing two degrees up - Jarvis, Andy (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Introducing the Two Degrees Up series of short climate change photofilms, highlighting the possible impact of rising temperatures on smallholder agriculture in Colombia, Ghana and Kenya. Narrated by Andy Jarvis, of CIAT - the lead center in the CGIAR's recently-launched Climate Change Research Program, or CCAFS.